2019
DOI: 10.5080/u23415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Childhood Adversities, Emotion Dysregulation and Cognitive Processes in Bipolar Disorder and Recurrent Depressive Disorder

Abstract: Bilişsel mekanizmalar gelişimsel dönemlerde çevresel zorlayıcı olaylardan etkilenebilir ve bilişsel çarpıtmalar ortaya çıkabilir. Bilişsel çarpıtmalar psikiyatrik hastalıkların klinik seyrini etkilemektedirler. Bu çalışmada bipolar bozukluk (BB) ve major depresif bozukluk-yineleyen dönemlerde (MDB-YD) çocukluk çağı travmaları (ÇÇT) ile duygu düzenleme güçlüğünün (DDG), otomatik düşünceler (OD) ve üstbilişler (ÜB) üzerindeki etkileri incelenmiştir. Yöntem: Çalışmamız 81 MDB-YD, 85 BB hastası ile 86 sağlıklı kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…In our study, it was observed that individuals both in the BD and MDD groups had significantly more difficulties in emotion regulation than the healthy controls. These results are consistent with previous findings (24,25). Studies are reporting that depression is a differentiation in emotion processing due to dysregulation of negative affect (26).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, it was observed that individuals both in the BD and MDD groups had significantly more difficulties in emotion regulation than the healthy controls. These results are consistent with previous findings (24,25). Studies are reporting that depression is a differentiation in emotion processing due to dysregulation of negative affect (26).…”
Section: Discussionsupporting
confidence: 93%
“…In studies comparing BD and MDD, the following comparisons became significant after the leave-one-out sensitivity analysis: (i) ‘ reflective pondering ’ subscale of the RRS, by removing the study (Aslan & Baldwin, 2021 ), (ii) ‘ putting into perspective ’ subscale of the CERQ, by removing the study (Wolkenstein, Zwick, Hautzinger, & Joormann, 2014 ), and (iii) ‘ goals ’ subscale of the DERS, by removing the study (Oymak Yenilmez et al, 2021 ), all passing from a small to a small-to-moderate effect size; (iv) ‘ awareness ’ subscale of the DERS, by removing the study (Musket, Hansen, Welker, Gilbert, & Gruber, 2021 ), passing from a small-to-moderate to a moderate effect size. On the contrary, by removing the studies ([Becerra et al, 2013 ], [Becerra, Bassett, & Harms, 2016 ], or [Weintraub, Van de Loo, Gitlin, & Miklowitz, 2017 ]) in the comparison relative to the ‘ clarity ’ subscale of the DERS, the overall effect became nonsignificant with an effect size comparable in magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…When the prediction intervals are the same as the confidence interval, the p-value is the same. In the two cases where the significant prediction intervals are different from the confidence intervals, their p-value is ≤ 0.01. comparisons related to each mentioned subscale): (i) in the 'putting into perspective' subscale of the CERQ, subsets including the study (Wolkenstein et al, 2014) presented higher heterogeneity and lower effect size; (ii) in the 'positive refocusing' subscale of the CERQ, subsets including the study (Ariana Kia & Hasani, 2014) presented higher heterogeneity and effect size; (iii) in the 'refocus on planning' subscale of the CERQ, subsets including the study (Kjaerstad et al, 2016) presented higher heterogeneity and effect size; (iv) in the 'goals' subscale of the DERS, subsets including the study (Oymak Yenilmez et al, 2021) presented higher heterogeneity and opposite effect size; (v) in the 'non acceptance' subscale of the DERS, subsets including the study (Oymak Yenilmez et al, 2021) presented higher heterogeneity and opposite effect size; and (vi) in the 'awareness' subscale of the DERS, subsets including the study (Musket et al, 2021) presented higher heterogeneity and lower effects size. By inspecting the GOSH plots in the studies comparing BD and BPD and exploring differences in the total DERS score, subsets including the study (Das, Calhoun, & Malhi, 2014) presented higher heterogeneity and effect size.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 In addition, studies have shown that childhood trauma can predict worse cognitive function in people with depressive disorders and bipolar disorder. 33 …”
Section: Discussionmentioning
confidence: 99%